Alyssum Cinsine Ait Bazı Taksonların Polen Morfolojisi - Doğan, Gülden; Yılmaz, Dilara Celayir; Demirpolat, Azize; Kıran, Yaşar; Doğan, Serkan (Uğur ÇAKILCIOĞLU, 2025)
In this study, genera of Alyssum from the family Brassicaceae, A. condensatum subsp. flexibile (Nyár.) T.R. Dudley, A. filiforme Nyár., A. xanthocarpum Boiss., A. simplex Rudolph, A. macropodum Boiss. & Balansa, A. contemptum Schott & Kotschy, A. trichostachyum Rupr., A. callichorum Boiss. & Balansa, A. strigosum subsp. strigosum Banks & Sol., A. strictum Willd., A. praecox Boiss. & Balansa and A. peltarioides subsp. virgatiforme (Nyár.) T.R.Dudley taxa the morphologies of the pollen were revealed using light microscopy (LM) and scanning electron microscopy (SEM). As a result of this study, some common features were found in pollen such as monad, radial symmetry, isopolar, pollen shapes being mainly subprolate and prolate, aperture type tricolpate and exine tectate. SEM microphoto also indicated that ornamentation structures were reticulate.

: In this study, genera of Alyssum from the family Brassicaceae, A. condensatum subsp. flexibile (Nyár.) T.R. Dudley, A. filiforme Nyár., A. xanthocarpum Boiss., A. simplex Rudolph, A. macropodum Boiss. & Balansa, A. contemptum Schott & Kotschy, A. trichostachyum Rupr., A. callichorum Boiss. & Balansa, A. strigosum subsp. strigosum Banks & Sol., A. strictum Willd., A. praecox Boiss. & Balansa and A. peltarioides subsp. virgatiforme (Nyár.) T.R.Dudley taxa the morphologies of the pollen were revealed using light microscopy (LM) and scanning electron microscopy (SEM). As a result of this study, some common features were found in pollen such as monad, radial symmetry, isopolar, pollen shapes being mainly subprolate and prolate, aperture type tricolpate and exine tectate. However, it was determined that the pollen shape in A. contemptum species is prolate-spheroidal unlike other species. In addition, the largest pollens were found in A. xanthocarpum and A. strigosum species, and the smallest pollens were found in A. peltarioides subsp. virgatiforme and A. callichorum species. SEM microphoto also indicated that ornamentation structures were reticulate.
Pollen Morphologies of Some Taxa of the Genus Alyssum L. (Brassicaceae)
Keywords: Botany (Other); Bitki Bilimi (Diğer)